Electrochemical determination of dopamine using Ni Pd bimetallic nanoparticles decorated on MWCNT: an amperometric sensor - Singh K.; Maurya K.K.; Malviya M. (My University, 2025)
In this study, we produced a nanocomposite composed of Ni-Pd bimetallic nanoparticles with precise morphologies that are adorned on multiwall carbon nanotubes. Electrochemical impedance spectroscopy (EIS), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) were used to evaluate the produced material. FE-SEM and HR-TEM analysis confirmed the uniform distribution of Ni-Pd across f-MWCNT surfaces. The findings reveal that incorporating Ni-Pd nanoparticles on the surface of f-MWCNT can improve catalytic activity over Ni NPs. The manufactured electrode has garnered a lot of interest in detecting and quantifying dopamine because of its demonstrated potential for instantaneous response, real-time measurements, increased selectivity, and sensitivity. Dopamine (DA) electrochemical activity in the presence of phosphate buffer solution (PBS) as an electrolyte at pH 7 was tested utilizing CV, DPV, and amperometry techniques to explore the sensor’s performance. The finding presented here reveals a simple strategy for creating a modified electrode. The Ni-Pd/f-MWCNT-modified electrode sensor reveals a wide linear range of dopamine (2–400 µM), with a limit of detection (LOD) 0.05 µM, limit of quantification (LOQ) 0.166 µM, and sensitivity 2.116 µA/µM cm2. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer Nature B.V. 2024.